Developing Citizens: The Impact of Civic Learning Opportunities on Students' Commitment to Civic Participation - Kahne, Joseph E.; Sporte, Susan E. (American educational research journal, 2008)
This study of 4,057 students from 52 high schools in Chicago finds that a set of specific kinds of civic learning opportunities fosters notable improvements in students' commitments to civic participation. The study controls for demographic factors, preexisting civic commitments, and academic test scores. Prior large-scale studies that found limited impact from school-based civic education often did not focus on the content and style of the curriculum and instruction. Discussing civic and political issues with one's parents, extracurricular activities other than sports, and living in a civically responsive neighborhood also appear to meaningfully support this goal. Other school characteristics appear less influential.